2011
DOI: 10.1111/j.1468-3083.2011.04260.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact hypersensitivity in rosacea – a study in 82 patients

Abstract: EditorThere are only few data concerning the frequency of contact hypersensitivity (CH) in rosacea, 1-5 although it in fact can play an important role in the therapy or in the daily life of the patients.The aim of this study was to map the ratio of CH in 82 unselected rosacea patients (68 women, 14 men, over all 18 years, mean age: 54.4) tested in the Department of Dermatology, Venerology and Dermato-oncology of the Semmelweis University between January 2004 and December 2009.The patch tests were performed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…They stated that contact allergy due to cosmetics could play a role in rosacea pathogenesis. Pónyai et al 13 found contact hypersensitivity in 35.4% of 82 rosacea patients. We found a positive reaction to at least 1 allergen in 32.3% of the patient group and 20% of the control group with the European standard series while these rates were 30.8% and 10% respectively with the cosmetic series.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…They stated that contact allergy due to cosmetics could play a role in rosacea pathogenesis. Pónyai et al 13 found contact hypersensitivity in 35.4% of 82 rosacea patients. We found a positive reaction to at least 1 allergen in 32.3% of the patient group and 20% of the control group with the European standard series while these rates were 30.8% and 10% respectively with the cosmetic series.…”
Section: Discussionmentioning
confidence: 98%
“…Contact hypersensitivity towards the ingredients of medical creams was positive at a rate of 27.8%. They concluded that the contact hypersensitivity in rosacea patients was mostly towards cosmetics 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only limited data have been published regarding contact sensibilization in rosacea patients. [12][13][14][15] Our data suggest that patch testing should be performed more often in rosacea patients, particularly in case of worsening of skin symptoms due to topical treatments or cosmetics. Patch testing may be helpful before administration of local therapies as well.…”
mentioning
confidence: 79%
“…Contact allergies contribute to the progression of the skin disease. 6,[12][13][14][15][16] We performed a retrospective cohort study on a total of 143 rosacea patients who were patch-tested at the Allergology Outpatient Unit of the Department of Dermatology, Venerology and Dermatooncology of Semmelweis University. Testing was performed for suspected contact allergy based on therapy resistance or on the patients' own observations that some topical medication or cosmetics had worsened the skin lesions.…”
mentioning
confidence: 99%